Mapping and Classification of upland soils Formed from Peninsular Gneiss in Rasipuram Block, Namakkal District of Tamil Nadu - Balasubramanian, V.; Ragunath, K. P.; Srinivasan, R.; Manikandan, E.; Suresh, K. (International Journal of Bio-resource and Stress Management, 2020)
A detailed soil survey was carried out in Rasipuram block of Namakkal district, Tamil Nadu, India consists of 24 villages spread over 10614 hectares. Based on variation in physiography and landform, eight soil series and 30 soil mapping units were identified. Eight typifying pedons were analysed for physical and physico-chemical properties and thus used for soil mapping at 1:10000 scale. Soils are shallow to very deep, well drained to somewhat poorly drained, light to dark reddish colour at moist condition, light (sandy loam) to heavy (clay) texture. The pH, EC, organic carbon and cation exchange capacity ranged from 7.4 to 9.4, 0.05 to 0.60 dS m-1, 0.2 to 0.7%, 0.11 to 0.60% and 10 to 45 c mol (p+) kg-1, respectively. The detailed classification of the soils from study area was Inceptisols and Alfisols soil order. The land capability classification grouping study in the study area indicates that marginally cultivable soils (IVs) covered 7.05% area was affected with severe limitations of erosion, whereas extent of moderate limitations of slight erosion and calcareousness (IIIc) was 77.34%. The erosion and calcareousness land covering 65.6% (IIIs) of the area were moderately suitable for sustained use under irrigation, provided proper soil and water conservation measures to be adopted.